Red, White, and Blue : A Critical Analysis of Constitutional Law - Tushnet, Mark, 1945- (Book collections on Project MUSE., 2015)
"The power of the Supreme Court to rule actions of Congress, the President, or the states unconstitutional is seemingly an undemocratic aspect of our system. The rationale for this power and how it should be exercised by the Court has produced over our history a series of debates and theories of constitutional law, the most recent being the on-going controversy over originalism. In this book Mark Tushnet critiques the grand theories of constitutional law, arguing that they all fail to explain the Constitution or guide the Court in its application across the wide range of cases it deals with, creating a firestorm of critical commentary. This new edition includes a foreword by Sandy Levinson and an afterword by the author to this book that was published by Harvard in 1988"--